Embedded hard real-time scheduling algorithm based on task's resource requirement. (3rd January 2011) - Hu, Wei; Chen, Tianzhou; Xie, Bin; Yan, Like
The embedded systems are resource limited systems and response time is commonly one of the most important requirements. In this paper, we present a real-time scheduling algorithm based on task's resource requirements for embedded system. In embedded systems, the resources and tasks are restricted, especially in specific systems. The tasks can be divided into different sets according to their resource requirements. In the same set, specific scheduling algorithm can be selected to schedule the tasks according to the features of the set. Thus different sets can have different scheduling algorithms. Then the scheduling sequences can be calculated as preparation partly. It is more efficient for embedded specific system.